Pemberlakuan Diversi terhadap Anak di Pengadilan Negeri Jember dalam Perspektif UUPA dan Fiqh Jinayah - Aisyah Fitri Kholifah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2020)
Children are an inseparable part of the sustainability of a nation and state. Therefore children need to receive protection from any social changes that significantly affect children's values, behavior, and development. Not infrequently, there are cases where a child commits a crime. The concept of restorative justice through diversion has a vital role in legal certainty and guarantee for children not only in the present but also in the future for the welfare of the child's life. This is in line with the Islamic Sharia, which views that small children do not have the ability to think perfectly in the actions they take. So in his motions, a small child cannot be punished like an adult who commits a crime or offense. Therefore, even in Islamic law, the perpetrators of child crimes also receive forgiveness with specified conditions and criteria. This research was conducted at the Jember District Court. Research shows that; The implementation of the application of the approach through the concept of restorative justice has been very effective in preventing bad possibilities that will happen to the child's future or psychological trauma to the child. However, this concept certainly still protects the interests and justice of victims. In the research on the implementation of the restorative justice concept that the writer did in the field, there were still several obstacles in terms of victim diversion agreement so that the case was continued to the criminal justice Criminal acts committed by children that can be resolved with diversion are criminal acts that carry a sentence of fewer than seven years and are not a repetition of the criminal act.